Transcatheter Closure of Perimembranous and Intracristal Ventricular Septal Defects Using Amplatzer Duct Occluder II in Children - Shenrong Liu; Wenqian Zhang; Junjie Li; Shushui Wang; Mingyang Qian; Jijun Shi; Yumei Xie; Zhiwei Zhang (Journal of Interventional Cardiology)
Background. Transcatheter closure of aneurysmal perimembranous ventricular septal defect (pmVSD), pmVSD near the aortic valve, and intracristal VSD (icVSD) with symmetrical or asymmetrical ventricular septal defect occluders still presents significant challenges. We report our experience with transcatheter closure of pmVSD and icVSD using Amplatzer duct occluder II (ADO II) in children. Method. We retrospectively analyzed all children, who presented to our hospital consecutively between March 2014 and June 2020 for attempted transcatheter closure of pmVSD or icVSD with the ADO II device. Standard safety and last-follow-up outcomes were assessed and compared. Results. In total, 41 patients underwent transcatheter closure of VSD with the ADO II (28 in pmVSD and 13 in icVSD groups) with a median age of 3.5 years (total range: 0.9 to 12 years) and median weight of 15.0 kg (total range: 10.0 to 43.0 kg). Implantation was successful in 40/41 patients (97.5%, 27/28 in pmVSD group, 13/13 in icVSD group). One patient with mild aortic valve prolapse in pmVSD group developed new-onset moderate aortic regurgitation after a 4/4 mm ADO II was deployed; however, this resolved after the device was retrieved and successfully replaced with a 5 mm zero eccentric VSD occluder. There was no procedure-related mortality. After a median follow-up of six months (total range: 6 to 72 months), complete closure rates were 85.1% and 76.9% among pmVSD and icVSD groups, respectively. In the pmVSD group, one case of new-onset moderate tricuspid regurgitation was observed at six months, and there was one case of severe tricuspid regurgitation that had progressed from mild tricuspid regurgitation at 12 months. No serious complications were noted in the icVSD group. Conclusion. ADO II provides a safe and reproducible alternative for the closure of perimembranous and intracristal ventricular septal defects with a diameter less than 5 mm in young children.